Job attitudes between unionized and non-unionized employees - Chang, Joshua; Travaglione, A.; O Neill, G. (Emerald, 2017)
Purpose: The purpose of this paper is to study job attitudes between unionized and non-unionized employees in Australia as recent research on attitudes among unionized employees has centred on topics such as attitudes towards unionization and involvement, but not on work-related attitudes. Design/methodology/approach: This study uses a data set of over 5,000 responses from the Australia at Work survey. Ten attitudinal survey questions adapted from the Australian Workplace Industrial Relations Survey and the Australian Survey of Social Attitudes were used to compare work-related attitudinal differences between unionized and non-unionized employees. Findings: Findings show that unionized employees perceive less manager–employee consultation, health and safety, dispensability, time flexibility, workload flexibility, managerial trust, fair treatment and pay equity. Originality/value: Not much is known about the attitudinal differences between unionized and non-unionized employees, given the paucity of research on unionist job attitudes. Recent research in this area has centred on employee attitudes towards unionization and involvement as opposed to studying work-related attitudes. The findings can help the management predict behavioural responses between unionized and non-unionized employees for improved decision making.